Preparation and Characterization of Activated Carbons from Parthenium biomass by Physical and Chemical Activation Techniques - Rajeshwari Sivaraj; Venckatesh Rajendran; G. Sangeetha Gunalan (E-Journal of Chemistry)
Parthenium hysterphorous (Linn), a perennial weed of no known beneficial use was introduced as a containment of food grains imported from US with P1480 scheme. The colonization efficiency of the weed was much higher than other indigenous weeds resulting in the reduction of cultivable areas of agricultural lands. Therefore, attention was focused to find out the potential use of its biomass. In the present study the preparation and characterization of activated carbons by physical and chemical activation methods are reported and aims to prepare relatively well developed porous activated carbons as well as study various conditions and parameters that were involved during the process. Among the carbons prepared Zncl2 impregnated carbon at the ratio of 1 was found to possess the characteristic features of an efficient adsorbent. Experimental results showed that pyrolytic and activation conditions leading to various final average temperatures had significant effect on the properties of activated carbons prepared.